Safety of calcium and vitamin D supplements, a randomized controlled trial. (1st October 2018) - Aloia, John F.; Katumuluwa, Subhashini; Stolberg, Alexandra; Usera, Gianina; Mikhail, Mageda; Hoofnagle, Andrew N.; Islam, Shahidul
Abstract: Objective: It is anticipated that an intake of vitamin D found acceptable by Endocrine Society Guidelines (10 000 IU/day) with co‐administered calcium supplements may result in frequent hypercalciuria and hypercalcaemia. This combination may be associated with kidney stones. The objective of this study was to compare the episodes of hypercalciuria and hypercalcaemia from calcium supplements co‐administered with 10 000 IU or 600 IU vitamin D daily. This design allows a comparison of the Institute of Medicine recommendation for the RDA of vitamin D along with the upper limit of calcium intake with the high intake of vitamin D suggested by the Endocrine Society. Context: Harms of currently recommended high intake of vitamin D have not been studied. Design: The design was a randomized controlled trial with 2 groups with evaluation every 3 months for one year: (a) CaCO3 1200 mg/day with 10 000 IU vitamin D3 /day or (b) CaCO3 1200 mg/day with 600 IU vitamin D3 /day. Patients: This study was conducted in an ambulatory research centre in healthy, white postmenopausal women. Measurements: Serum and 24‐hour urine calcium were measured. Results: Hypercalcaemia and hypercalciuria occurred in both groups. At the final visit, 19/48 in the high dose D group had hypercalciuria. The odds of developing hypercalciuria were 3.6 [OR = 3.6(1.39, 9.3)] times higher in the high dose D group. The odds of developing hypercalcaemia did not differ between groups. Conclusions: The safe upper level of vitamin D recommended by the Endocrine Society when accompanied by calcium supplements results in frequent hypercalciuria. The risk of kidney stones at these levels should be investigated.